How does a Politician Build a Political Image on Instagram? - Abraham Zakky Zulhazmi; Muh Galih Nirboyo (Universitas Darussalam Gontor, 2022)
Nowadays, social media image shaping is massively carried out by politicians. The wide range of internet network distribution and low cots needed have made these easier for a political actor to execute their political strategies. Besides using social media as a medium to interact with the citizen, they also use it as medium to build their political image. This research uses the semiotic analysis method.The researcher chose the semiotic method from Roland Barthes for the methode of analysis. This study found that Sri Mulyani used her Instagram account as a medium to forming her political image. The verbal or non-verbal symbols where she displays through her uploads on her Instagram account are aimed to shape her political image. Image of Sri Mulyani on her Instagram, based on Anwar Arifin, political image theory, which includes influence, authority, power or force, corporation, conflict and consensus. Sri Mulyani's political image on Instagram is influence, The image shaping that Sri Mulyani is trying to creat/build through her Instagram is a leader who is democratic, modest, religios, a populist who shows her care to SME, farmer, education, and the welfare of mother and children.